Prevalence of non-adherence to management plan and lifestyle advice among type 2 diabetes mellitus patients and its associated factors in rural north Kerala: a community based cross-sectional study - Thattarath Kottayi, Remya; Karunakaran, Usha (International Journal Of Community Medicine And Public Health, 2025)
Background: The prevalence of diabetes mellitus is increasing especially in developing countries, along with rise in obesity and sedentary lifestyle. The complication due to diabetes are also leading to serious public health problem. Methods: A community based cross sectional study conducted among 240 study participants with type 2 diabetes mellitus above 18 years in north Kerala. Four wards are selected by using cluster sampling. Data was collected by interview using semi structured questionnaire with scoring, then categorized as non-adherent and good adherent for medication, diet and physical activity. Results: There were 240 study participants with mean age of 63±9.42 years. 63% were having comorbidity other than Diabetes, among them HTN (50.7%) was most common followed by dyslipedmia.62% were taking treatment from public health sector. The duration of diabetes between 5 years and 10 years were 42.1% (majority). 19% were having complication. Among the 240 study participants only 7% were non adherent to medication, 34.5% to diet and 51.2% to physical activity. There was a significant association noted among non-adherence to physical activity in elderly age group and those who take treatment from government hospital. Those who were non adherent to diet had an unsatisfactory blood sugar value. Patients with short duration of diabetes, employed and those with no comorbidities were non adherent to medication. Conclusions: The study shows that only 7% participants are non-adherent to diabetic medication. But more than half of the participants are non-adherent to exercise and one third are non-adherent to diet.